Klasifikasi Lingual Jajanan Tradisional Desa Cemagi - Ni Nyoman Widani; Wiya Suktiningsih; Wahyu Kamil Syarifaturrahman (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
Lingual or language is an integral part of the cultural expression of a society, is used as a means of communicating values, beliefs and customs, has an important social function and fosters a sense of group identity and solidarity. Traditional Balinese snacks for the Cemagi Village society are not just food but also have an important role as a means of traditional ceremonies. A linguistic anthropology approach was used by researchers to reveal the culture of the Cemagi people, in the process of inheriting and passing on the role of traditional snacks in their beliefs as Hindus. It is hoped that the role of traditional snacks can be learned, inherited, passed on from one generation to the next, through actions in the form of face-to-face interactions, and of course through linguistic communication, both verbal and non-verbal. -verbal form. The proposed research is to find out how traditional food exists and to know the lexicon of traditional snacks and their meaning in a traditional ceremony. There were 12 lexicons found in this first research and explained in terms of processing processes and fields of meaning in the beliefs of the Cemagi society. Traditional snacks are used as the main filling material and function as a means in traditional ceremonial processions. Traditional snacks are symbolic and expressive, both in terms of shape, ingredients and taste.